VD_FINDINFO 296 vom 24. März 2022 - VD Tribunal cantonal (2022)
ESCROQUERIE, PRINCIPE DE L'ACCUSATION, FIXATION DE LA PEINE, SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE | 146 CP, 43 al. 1 CP, 47 CP, 49 al. 1 CP, 9 CPP (CH)